Does antenatal education reduce fear of childbirth? - POTUR, DİLEK; DEMİRCİ, NURDAN (WILEY, 2016)
AimThe aim of this study was to determine the effect of antenatal education on fear of childbirth, acceptance of pregnancy and identification with motherhood role. BackgroundThere is insufficient evidence pertaining to the effect of antenatal education on fear of childbirth, acceptance of pregnancy and identification with motherhood role. IntroductionThe purpose of antenatal education is to help couples make the right decisions during delivery. Through antenatal education, couples prepare themselves for delivery. MethodsThis is a quasi-experimental and prospective study that employs a pre- and post-education model. In total, 192 pregnant women (education group, n=69 and control group, n=123) participated in the study. Data were collected using the pregnancy identification form: the Prenatal Self-Evaluation Questionnaire and a version of the Wijma Delivery Expectancy/Experience Questionnaire. ResultsPrior to participating in the study, the education group and control group had similar levels of acceptance of pregnancy and identification with motherhood role, whereas a significant difference was found in their fear of childbirth levels. When surveyed again after receiving education, the two groups' levels of acceptance of pregnancy and fear of childbirth were found to be significantly different. However, they had similar levels of identification with the motherhood role. ConclusionAntenatal education appears to increase the acceptance of pregnancy, does not affect the identification with motherhood role and reduces the fear of childbirth. Implications for nursing and health policyA systematic antenatal education programme, as part of routine antenatal care services, would help reduce the rate of interventional labour and facilitate pregnant women's conscious participation in the act of labour by reducing their fear of childbirth.
Keywords: Antenatal Education; Fear of Childbirth; Midwife; Nurse; Pregnancy; Prenatal; Type of Birth; PREGNANT-WOMEN; W-DEQ; QUESTIONNAIRE; PERCEPTIONS; EXPERIENCES; OUTCOMES; PROGRAM